Students’ Experiences toward Scripted and Unscripted Role Playing in Junior High School - Romadhona, Ghorizah; Ahmad Munir; Rizqiyah, Anifatul (Institut Agama Islam Negeri Parepare, 2023)
This study has two main research objectives, namely, to find out the students’ experiences in scripted and unscripted role play and to find out which mode of role play, scripted or unscripted, better assist them to develop speaking competence. This research took two classes of seventh grades as the participant with each class had 34 students. Mixed qualitative and quantitative method was chosen to answer the research questions. The qualitative method used the observation and questionnaire as the instrument. The quantitative method used SPSS to test difference of speaking scores between the scripted and unscripted classes. One of the findings is that the students were doing well in preparing the role play such as, building sentences and understanding the role play card. Another finding is that they experienced difficulty during the role play performance. In evaluating role play, students got some positive impact. Also, the results showed that the students who did unscripted role play got better speaking scores than students who had scripted role play did. It can be concluded, even though they face some difficulties during the performance, students had some positive impact after doing role play and unscripted role play is better than scripted role play in assisting students speaking competence.